Gendered geographies of environmental injustice - Buckingham, Susan; Kulcur, Rakibe (Antipode, 2009)
As environmental justice concerns become more widely embedded in environmental organizations and policymaking, and increasingly the focus of academic study, the gender dimension dissolves into an exclusive focus on race/ethnicity and class/income. While grassroots campaigning activities were often dominated by women, in the more institutionalized activities of organizations dominated by salaried professionals, gender inequality is neglected as a vector of environmental injustice, and addressing this inequality is not considered a strategy for redress. This paper explores some of the reasons why this may be so, which include a lack of visibility of gendered environmental injustice; professional campaigning organizations which are themselves gender blind; institutions at a range of scales which are still structured by gender (as well as class and race) inequalities; and an intellectual academy which continues to marginalize the study of gender—and women's—inequality. The authors draw on experience of environmental activism, participant observation, and other qualitative research into the gendering of environmental activity, to first explore the constructions of scale to see how this might limit a gender-fair approach to environmental justice. Following this, the practice of “gender mainstreaming” in environmental organizations and institutions will be examined, demonstrating how this is limited in scope and fails to impact on the gendering of environmental injustice.
Keywords: approches et analyses; corps; discipline; environnement; géographie; intersectionnalité; justice environnementale; justice sociale; projet charge mentale; sciences humaines; thématiques

FéminismeS et diversitéS culturelleS - Institut de recherches et d'études féministes (FéminÉtudes, 2009)
Cette publication rend compte des réflexions féministes, théoriques et pratiques majoritaires dans une perspective décoloniale. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Disponible en libre accès : https://iref.uqam.ca/feminetudes/vol-14-no-1-2009-feminismes-et-diversites-culturelles/
Keywords: 2000 à aujourd'hui; 2000-2009; activisme; amériques; approches et analyses; corps; droits des femmes*; féminétudes; histoire et politique; intersectionnalité; militance; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; violences; violences contre les femmes*; écriture des femmes*

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Les tactiques féministes confrontées aux « tirs amis » dans le mouvement des femmes en Irlande - Taylor, Judith (Politix, 2007)
Cet article examine les modèles courants d’intelligibilité de l’interaction tactique entre les acteurs des mouvements sociaux et montre leur insuffisance pour rendre compte de l’invention tactique dont a dû faire preuve le mouvement des femmes en Irlande. Une analyse des efforts déployés par les féministes irlandaises pour l’extension du droit à l’avortement met en question l’idée que les innovations tactiques ne répondraient qu’aux contre-mouvements ou à la répression de l’État. L’expression « tir ami » fait référence au processus par lequel des groupes qui ne sont pas en opposition avec un mouvement, mais qui n’en font pas non plus partie, constituent une menace pour les finalités de ce mouvement. L’observation de la campagne féministe, de ses meetings et de l’ensemble de sa mise en scène politique donne des aperçus significatifs sur les effets des tirs amis et, spécifiquement, sur le rôle des hommes dans les mouvements de femmes.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; avortement; care; corps; cours; discipline; droits des femmes*; europe; intersectionnalité; irlande; justice reproductive; justice sociale; pol5185; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques

La sexualité entre sexisme et racisme: les descendantes de migrant·e·s du Maghreb et la virginité - Hamel, Christelle (Nouvelles Questions Féministes, 2006)
L'article présente le résultat d'une recherche sur la vie affective et sexuelle des jeunes Français-es descendant de migrant-e-s originaires du Maghreb, qui décrit comment les jeunes femmes se positionnent par rapport au principe de virginité. Alors que cette norme est un mode de contrôle de la sexualité des femmes, certaines le revendiquent, tandis que celles qui l'ont transgressé expriment combien cette décision leur fut difficile. Pour comprendre la prégnance de leur attachement à la valeur de la virginité, l'autrice replace leurs discours et pratiques dans le contexte social qui les a fait naître. Elle décrit donc comment les discriminations et la stigmatisation racistes façonnent l'expérience de vie de ces jeunes femmes et montre combien cette expérience du racisme se combine à l'expérience du sexisme dans les familles et dans la société globale. Ici, l'imbrication du sexisme et du racisme fait peser sur elles un système de contraintes complexe qui les soumet à des injonctions paradoxales. Ce n'est qu'au regard de ces injonctions que la revendication par certaines de cette norme qui par ailleurs les opprime devient intelligible.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; corps; cours; discipline; europe; france; histoire et politique; intersectionnalité; maghreb; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; virginité; études démographiques

The Politics of Protection: Body Image, Social Pressures, and the Misrepresentation of Young Black Women - Poran, Maya A. (Sex Roles : A Journal of Research, 2006)
As part of a larger multi-method study, 15 Black women college students participated in focus group discussions on the body. Contrary to popular theories that propose that Black women are protected by a “Black Culture” that buffers them from negative effects of body representations—thereby leaving them with higher body esteem—the themes that emerged in the focus group discussions indicate that young Black women are indeed feeling (1) pressures to be thin, (2) pressures from the preferences of men of diverse ethnicities, (3) competition with other Black women in the realms of beauty, and (4) a strong sense of being misrepresented by media images of thin Black women. These results not only indicate that body image issues are of real pressing concern to young Black women, but that psychological research methodologies may be adding to the misrepresentation of young Black women and their struggles. Qualitative methods must be utilized in order to hear more clearly the voices of Women of Color.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; image corporelle; intersectionnalité; new york; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; états-unis

Unveiled Sentiments: Gendered Islamophobia and Experiences of Veiling among Muslim Girls in a Canadian Islamic School - Zine, Jasmin (Equity & Excellence in Education, 2006)
The practice of veiling has made Muslim women subject to dual oppressions–racism and Islamophobia–in society at large and patriarchal oppression and sexism from within their communities. Based on a narrative analysis of the politics of veiling in schools and society, the voices of young Muslim women attending a Canadian Islamic school speak to the contested notion of gender identity in Islam. The narratives situate their various articulations of Islamic womanhood in ways that both affirm and challenge traditional religious notions. At the same time they also are subject to Orientalist representations of veiled and burqa clad women that represent them as oppressed and backward. Focusing on ethnographic accounts of veiling among Muslims girls who attended a gender-segregated Islamic high school in Toronto, this discussion allows a deeper understanding of how gendered religious identities are constructed in the schooling experiences of these Muslim youth. (Contains 11 notes.)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; corps; cours; discipline; féminisme islamique; intersectionnalité; islamophobie; ontario; patriarcat; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; toronto; voiles islamiques

Black sexual politics: African Americans, gender, and the new racism - Hill Collins, Patricia (Routledge, 2005)
To a large extent, scholarship on black politics often focuses primarily on institutions, rule of law, processes, political actors, and citizens but with very little attention to issues of gender and sexuality. In contrast, the principal aim of this book is to explore what the author sees as the inextricable links between racism and gender. The basic thesis of this well-written, important, and provocative book is that the fight against racism, especially the “new racism,” can never be won without first challenging sexism, which simultaneously oppresses African-American men and women.
Section: ix, 374 p. ; 23 cm
Keywords: afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; féminismes noirs; intersectionnalité; premier cycle; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; théorie critique de la race; violences; états-unis

Attitudes Toward Victims of Rape: Effects of Gender, Race, Religion, and Social Class - Nagel, Barbara; Matsuo, Hisako; McIntyre, Kevin P.; Morrison, Nancy (Journal of Interpersonal Violence, 2005)
Although previous literature focusing on perceptions of victims of rape has examined how gender, race, and culture influence the attitudes one holds toward victims, these studies have yielded mixed results. This study compared perceptions of victims of rape across a wide range of ages, educational backgrounds, religions, and income levels, while focusing on gender and racial differences. Results indicate (N = 220) that victims of rape are generally viewed more sympathetically by females than by males and by Whites than by African Americans. However, the effect of race disappears when socioeconomic variables are controlled, suggesting a more complex relationship. Also, a hierarchical regression indicates that age, sex, education, and income are significant predictors of attitudes toward victims. This study builds on existing research that examines such attitudes from a cultural perspective and extends this literature by examining the interactive effects of several demographic variables within a community sample.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Domestic violence at the intersections of race, class, and gender: challenges and contributions to understanding violence against marginalized women in diverse communities - Sokoloff, Natalie J; Dupont, Ida (Violence against women, 2005)
This article provides a comprehensive review of the emerging domestic violence literature using a race, class, gender, sexual orientation intersectional analysis and structural framework fostered by women of color and their allies to understand the experiences and contexts of domestic violence for marginalized women in U.S. society. The first half of the article lays out a series of challenges that an intersectional analysis grounded in a structural framework provides for understanding the role of culture in domestic violence. The second half of the article points to major contributions of such an approach to feminist methods and practices in working with battered women on the margins of society.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; care; corps; cours; criminologie; discipline; féminisme afroaméricain; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; violences; états-unis

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

"You Can Never Be Too Rich or Too Thin": Popular and Consumer Culture and the Americanization of Asian American Girls and Young Women - Lee, Stacey J.; Vaught, Sabina (The Journal of Negro Education, 2003)
First- and second-generation youth of color are vulnerable to racialized images of gender and sexuality as reflected in and perpetuated by dominant forms of popular and consumer cultures. These popular images inform the process of Americanization, including racialized sexualization, for first- and second-generation Americans. This paper examines the way first- and second-generation Asian American girls and young women interpret and reinterpret popular representations of their positions in the United States. Data from two qualitative studies on Asian American young women will be presented.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; corps; cours; discipline; féminisme pop; hmong; intersectionnalité; laos; premier cycle; périodes historiques; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Feminism and the body - Schiebinger, Londa (Oxford University Press, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Section: IX, 500 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme